# Calculus

Solve using chain rule

y=(3x^3+1)(-4x^2-3)^4

So far, I have:

y'=(3x^3+1)*4(-4x^2-3)^3*(-8x)+(-4x^2-3)^4*(9x^2)

1. 0
2. 1
1. fine so far

posted by Damon

## Similar Questions

1. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?? i'm having trouble discerning
2. ### Math (Calculus)

Hello, Could somebody please help me with the following question? It asks to differentiate the function below according to derivate rules of calculus such as the power rule (if f(x)=x^n, then f'(x)=nx^n-1), the product rule (if
3. ### calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the
4. ### Differentiation

How do you find f'(x), f''(x) of f(x) =ln (1-x) IF f(x) = ln (1-x) Then use the chain rule with u(x) = 1-x f(u) = ln u df/dx = df/du du/dx f'(x) = -1/(1-x) Use the chain rule again: f"(x) = -[-1/(1-x)^2]*(-1) = -1/(1-x)^2 What is
5. ### MoRe HeLp PlEaSe!! (calc)

Also can I get some help with this LONG, TIRESOME PROBLEM? Find the derivative using the chain rule. f(x)= ((3x-7)/(6x+3))^4 Thanks a lot! (68/(12x^2+12x+3))*[(3x-7)/(6x+3)]^3 you should double check the answer multiply
6. ### Calculus

Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)-f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx
7. ### Math - Calculus Question.

hey can someone explain to me the relationship between the chain rule and implicit differentiation? It would be very much appreicated, thanks The chain rule is utilized whenever you have a function within a function such as cos^2
8. ### calculus

Find dz/dy and dz/dx Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm
9. ### calculus

Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the
10. ### calculus

Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the

More Similar Questions